A negative electrode material, a preparation method therefor, and an application thereof
Patent Information
- Application Number
- CN202610319681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-03-17
AI Technical Summary
[0005]本发明的目的是为了克服现有技术存在的负极材料无法兼顾在保证高容量的同时,降低硅碳材料用量和整体成本,同时改善电解液浸润性,提高循环稳定性的缺陷,提供一种负极材料及其制备方法和应用,本发明的结构能够改善电解液浸润性与离子导通效率,提升倍率性能与循环寿命,电池的容量提升,材料成本显著下降,循环稳定性增强
[0027]本发明通过上述技术方案,尤其是依次设置的碳/非晶硅交替层、硅碳复合层,碳/非晶硅交替层中所含非晶硅层作为高容量主承载层、用于提升容量,碳层作为缓冲层与应力释放层,二者交替设置形成应力缓冲体系,能够在保持电解液高容量承载的同时,有效缓解非晶硅纵向膨胀,降低体积膨胀导致的电极粉化,还配合硅碳复合层,建立离子通道匹配,改善电解液浸润性与离子导通效率,提升倍率性能与循环寿命,提升整体电化学稳定性,实现在硅碳复合层较薄、用量低(其厚度可低于15µm,用量远低于传统硅碳负极的厚度一般为40µm)的情况下,提高界面接触性,大大提升电解液浸润性,并有效避免不良腐蚀反应以及非晶硅过度膨胀的情况,从而提升电池能量密度和循环稳定性,材料成本显著降低。且,本发明负极材料使得电池整体比容量起步可达2000 mAh/g以上,显著优于传统硅碳材料(800-1200 mAh/g);且本发明利用部分碳/非晶硅交替层中所含的硅膜贡献的容量,进行减少硅碳复合层的用量,硅碳材料用量减少至原来的1/4–1/5,材料成本显著降低;整体负极成本趋近于石墨水平。
Smart Images

Figure CN121905791B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of negative electrode material technology, specifically relating to a negative electrode material, its preparation method, and its application. Background Technology
[0002] Currently, the demand for high-energy-density anode materials for lithium-ion batteries is constantly increasing. Traditional graphite anodes have limited specific capacity (approximately 370 mAh / g), making it difficult to meet the energy density requirements of next-generation batteries. Although silicon-based anodes have the advantage of high specific capacity (theoretically 4200 mAh / g), they suffer from severe volume expansion (over 300%) and poor electrolyte wettability.
[0003] To address this, existing technologies mostly employ silicon-carbon composite materials for the anode (with a silicon content below 30 wt%), but several problems remain: 1. High silicon-carbon usage leads to high costs (400,000–600,000 RMB / ton); 2. Limited silicon content in the anode results in actual capacities typically between 800–1200 mAh / g. Given the high cost of silicon-carbon anodes, higher silicon content is desirable to increase energy density, but this comes at the cost of high costs and the volume of silicon cannot be increased indefinitely due to its tendency to expand; 3. The expansion of amorphous silicon can lead to electrode pulverization, breakage of the conductive network between active particles, and peeling of the active layer from the current collector, resulting in poor electrolyte wettability and cycle stability. Therefore, how to reduce silicon-carbon material usage and overall cost while ensuring high capacity, and simultaneously improve electrolyte wettability and cycle stability, is a pressing problem that needs to be solved in this field.
[0004] It should be noted that this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or known technology. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing negative electrode materials that cannot simultaneously ensure high capacity, reduce the amount of silicon-carbon materials and overall cost, improve electrolyte wettability, and enhance cycle stability. This invention provides a negative electrode material, its preparation method, and its application. The structure of this invention can improve electrolyte wettability and ion conduction efficiency, enhance rate performance and cycle life, increase battery capacity, significantly reduce material costs, and enhance cycle stability.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a negative electrode material comprising a copper-containing substrate, wherein a carbon / amorphous silicon alternating layer and a silicon-carbon composite layer are sequentially disposed on the copper-containing substrate, the carbon / amorphous silicon alternating layer comprising alternating carbon layers and amorphous silicon layers; wherein the total thickness of the carbon / amorphous silicon alternating layer is 3-15µm, and the thickness of the silicon-carbon composite layer is 5-15µm.
[0007] In some preferred embodiments of the present invention, in the carbon / amorphous silicon alternating layer, the total number of carbon layers is 1-3 layers and the total number of amorphous silicon layers is 1-3 layers.
[0008] In some preferred embodiments of the present invention, in the carbon / amorphous silicon alternating layer, the total number of carbon layers is greater than the total number of amorphous silicon layers.
[0009] In some preferred embodiments of the present invention, the thickness of the monolayer carbon layer is 30-1000 nm, and the thickness of the monolayer amorphous silicon layer is 1-5 µm.
[0010] In some preferred embodiments of the present invention, the thickness of the plurality of carbon layers contained in the carbon / amorphous silicon alternating layer is arranged in a gradient increasing manner in the direction away from the copper-containing substrate.
[0011] In some preferred embodiments of the present invention, in the direction away from the copper-containing substrate, the carbon / amorphous silicon alternating layer sequentially comprises a first carbon layer, a first amorphous silicon layer, a second carbon layer, a second amorphous silicon layer, and a third carbon layer, wherein the thickness of the first carbon layer and the second carbon layer is independently 30-200 nm, and the thickness of the third carbon layer is 200-1000 nm.
[0012] In some preferred embodiments of the present invention, the thickness of the second carbon layer is less than the thickness of the third carbon layer, and the thickness of the second carbon layer is not greater than the thickness of the first carbon layer; and / or, the thickness of the second carbon layer is 30-100 nm.
[0013] In some preferred embodiments of the present invention, the outermost layer of the carbon / amorphous silicon alternating layer is a carbon layer, and / or the material of the carbon layer includes at least one of amorphous carbon, hydrogenated amorphous carbon, and nitrogen-doped carbon.
[0014] Preferably, the negative electrode material further includes a protective layer disposed between the copper substrate and the carbon / amorphous silicon alternating layer, the protective layer including a titanium nitride layer, the thickness of the protective layer being 10-100 nm.
[0015] In some preferred embodiments of the present invention, the protective layer further includes a titanium layer located on the side of the titanium nitride layer away from the copper-containing substrate; wherein the thickness ratio of the titanium layer to the titanium nitride layer is (0.1-0.7):1, and / or the thickness of the titanium layer is 5-20 nm, and the thickness of the titanium nitride layer is 30-80 nm.
[0016] In some preferred embodiments of the present invention, the silicon content in the silicon-carbon composite layer is 5-20 wt%; and / or, the copper-containing substrate includes copper foil.
[0017] In a second aspect, the present invention provides a method for preparing a negative electrode material, which is used to prepare the negative electrode material described in the first aspect. The preparation method includes: depositing a carbon / amorphous silicon alternating layer on the surface of a copper-containing substrate, and then forming a silicon-carbon composite layer on the surface of the carbon / amorphous silicon alternating layer; wherein, the process of depositing the carbon / amorphous silicon alternating layer includes alternating deposition of carbon layers and amorphous silicon layers.
[0018] In some preferred embodiments of the present invention, the preparation method further includes at least one of the following processes:
[0019] Process 1, the preparation method also includes: depositing a protective layer between the copper-containing substrate and the silicon-carbon composite layer, the process of depositing the protective layer includes: depositing a titanium nitride layer or sequentially depositing a titanium nitride layer and a titanium layer;
[0020] Process 2: Deposition of alternating carbon / amorphous silicon layers is performed using PECVD technology at a temperature of 200-500℃.
[0021] Process 3: The silicon-carbon composite layer is formed by coating.
[0022] Thirdly, the present invention provides a lithium battery comprising a positive electrode material, a negative electrode material as described in the first aspect, a separator, and an electrolyte.
[0023] In some preferred embodiments of the present invention, the cathode material is a lithium manganese iron phosphate cathode material, which includes a lithium manganese iron phosphate matrix and a carbon coating layer covering the surface of the lithium manganese iron phosphate matrix; the chemical formula of the lithium manganese iron phosphate matrix is Li. a Fe x Mn y M j PO q Wherein, M includes at least one of Al, Mg, Cu, Co, Ni, Nb, V, Ti, and La; 0.8≤a≤1.2, 0.1≤x≤0.9, 0.1≤y≤0.9, 0≤j≤0.1, and 4≤q≤5; the mass of the carbon coating layer accounts for 0.5%-3% of the total mass of the lithium manganese iron phosphate cathode material.
[0024] In some preferred embodiments of the present invention, the electrolyte comprises an electrolyte, an additive, and a solvent, wherein the electrolyte comprises lithium hexafluorophosphate.
[0025] Fourthly, the present invention provides an electrical device comprising the lithium battery described in the third aspect.
[0026] Beneficial effects:
[0027] This invention, through the above-mentioned technical solution, particularly the sequential arrangement of a carbon / amorphous silicon alternating layer and a silicon-carbon composite layer, utilizes the amorphous silicon layer in the carbon / amorphous silicon alternating layer as a high-capacity main bearing layer to enhance capacity, and the carbon layer as a buffer layer and stress relief layer. The alternating arrangement of these two layers forms a stress buffer system, which can effectively alleviate the longitudinal expansion of amorphous silicon while maintaining high electrolyte capacity, reducing electrode pulverization caused by volume expansion. Furthermore, in conjunction with the silicon-carbon composite layer, it establishes ion channel matching, improves electrolyte wettability and ion conduction efficiency, enhances rate performance and cycle life, and improves overall electrochemical stability. This allows for improved interfacial contact and significantly enhanced electrolyte wettability while using a thin silicon-carbon composite layer (its thickness can be less than 15µm, far lower than the typical 40µm thickness of traditional silicon-carbon anodes). It also effectively avoids adverse corrosion reactions and excessive expansion of amorphous silicon, thereby improving battery energy density and cycle stability, and significantly reducing material costs. Furthermore, the anode material of this invention enables the overall specific capacity of the battery to start at over 2000 mAh / g, which is significantly better than traditional silicon-carbon materials (800-1200 mAh / g). Moreover, this invention utilizes the capacity contributed by the silicon film contained in part of the carbon / amorphous silicon alternating layer to reduce the amount of silicon-carbon composite layer used, reducing the amount of silicon-carbon material used to 1 / 4-1 / 5 of the original, and significantly reducing material costs; the overall anode cost is close to the level of graphite.
[0028] In this invention, the thickness of the carbon / amorphous silicon alternating layer and the silicon-carbon composite layer are controlled within the above-mentioned suitable range, which can effectively buffer the volume expansion of amorphous silicon during lithium insertion / delithiation, prevent the electrode structure from collapsing, maintain the tight bonding between the active layer and the current collector, improve electrolyte wetting and ion diffusion channels, and help improve energy density while improving cycle life and electrochemical stability.
[0029] In a preferred embodiment of the present invention, the negative electrode material further includes a protective layer disposed between the copper-containing substrate and the carbon / amorphous silicon alternating layer. The titanium nitride layer contained in the protective layer serves as a dense protective layer between the carbon / amorphous silicon alternating layer and the copper-containing substrate, which can prevent the copper in the copper-containing substrate from reacting with the electrolyte and corroding it, and provides low contact resistance and high stability, thereby further improving the battery energy density and cycle stability.
[0030] In the preparation method of the present invention, the film layer can be deposited by PCVD (deposition temperature of about 200-500℃, for example, low temperature deposition of 200-250℃), which can realize large-area continuous deposition, has roll-to-roll mass production potential, meets industrialization needs, is suitable for roll-to-roll PCVD, and has the potential for large-scale preparation and commercialization. Attached Figure Description
[0031] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 This is a schematic diagram of a specific embodiment of the present invention.
[0033] Explanation of reference numerals in the attached figures
[0034] 1. Copper foil; 2. Protective layer; 3. Carbon / amorphous silicon alternating layer; 31. First carbon layer; 32. First amorphous silicon layer; 33. Second carbon layer; 34. Second amorphous silicon layer; 35. Third carbon layer; 4. Silicon-carbon composite layer. Detailed Implementation
[0035] In this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0036] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0037] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges. For numerical ranges, the endpoint values of the ranges, the endpoint values of the ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "optional" mean that they may or may not be included (or may or may not be present).
[0038] In a first aspect, the present invention provides a negative electrode material, comprising a copper-containing substrate, and a carbon / amorphous silicon alternating layer and a silicon-carbon composite layer sequentially disposed on the copper-containing substrate, wherein the carbon / amorphous silicon alternating layer comprises alternating carbon layers and amorphous silicon layers.
[0039] Preferably, the total thickness of the carbon / amorphous silicon alternating layer is 3-15µm, specifically 3µm, 3.5µm, 4µm, 4.5µm, 5µm, 5.5µm, 5.7µm, 6µm, 6.5µm, 7µm, 7.5µm, 8µm, 8.5µm, 9µm, 9.5µm, 10µm, 10.5µm, 11µm, 11.5µm, 12µm, 12.5µm, 13µm, 13.5µm, 14µm, 14.5µm, or 15µm, as well as any range between two point values.
[0040] Preferably, the thickness of the silicon-carbon composite layer in this invention is 5-15µm, specifically 5µm, 5.5µm, 6µm, 6.5µm, 7µm, 7.5µm, 8µm, 8.5µm, 9µm, 9.5µm, 10µm, 10.5µm, 11µm, 11.5µm, 12µm, 12.5µm, 13µm, 13.5µm, 14µm, 14.5µm, or 15µm, or any range between two point values.
[0041] In some preferred embodiments of the present invention, the thickness of the silicon-carbon composite layer is 5-10 µm. The anode material of the present invention can achieve high capacity and improved cycle stability with only a thin silicon-carbon composite layer (far less than the 40 µm thickness of conventional silicon-carbon composite materials).
[0042] In some preferred embodiments of the present invention, the silicon content in the silicon-carbon composite layer is 5-20 wt%, specifically 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, or 20 wt%, as well as any range between any two values.
[0043] In this invention, the alternating arrangement of carbon layers and amorphous silicon layers in the carbon / amorphous silicon alternating layer refers to their alternating arrangement in the thickness direction. Specifically, this can be a multiple alternating arrangement, a single alternating arrangement, or an alternating arrangement of a sandwich structure, such as a carbon layer, an amorphous silicon layer, and a carbon layer arranged sequentially. In some preferred embodiments of this invention, the total number of carbon layers in the carbon / amorphous silicon alternating layer is 1-3 layers (e.g., 1, 2, or 3 layers), and the total number of amorphous silicon layers is 1-3 layers (e.g., 1, 2, or 3 layers). The number of carbon layers and amorphous silicon layers can be the same or different.
[0044] In some preferred embodiments of the present invention, in the carbon / amorphous silicon alternating layer, the total number of carbon layers is greater than the total number of amorphous silicon layers. Preferably, the total number of carbon layers is greater than the total number of amorphous silicon layers, which is more conducive to effectively mitigating the longitudinal expansion of amorphous silicon, reducing electrode pulverization caused by volume expansion, improving electrolyte wettability and ion conduction efficiency, enhancing rate performance and cycle life, and improving overall electrochemical stability.
[0045] In some preferred embodiments of the present invention, the outermost layer of the carbon / amorphous silicon alternating layer is a carbon layer.
[0046] In some preferred embodiments of the present invention, the thickness of the single carbon layer is 30-1000 nm, specifically, it can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm or 1000 nm, or any range between two point values.
[0047] Preferably, the thickness of the single-layer amorphous silicon layer is 1-5µm, for example, it can be 1µm, 1.5µm, 2µm, 2.5µm, 3µm, 3.5µm, 4µm, 4.5µm or 5µm, or any range between two point values.
[0048] In some preferred embodiments of the present invention, the thickness of the multiple carbon layers contained in the carbon / amorphous silicon alternating layer increases in a gradient direction away from the copper-containing substrate. This preferred approach facilitates the gradual release of volume expansion stress in the amorphous silicon during charge and discharge processes, forming a transitional structure from the inside out. This improves interlayer bonding stability, prevents crack propagation and pulverization, and further enhances the overall mechanical integrity and cycle durability of the electrode.
[0049] In some preferred embodiments of the present invention, in the direction away from the copper-containing substrate, the carbon / amorphous silicon alternating layer sequentially comprises a first carbon layer, a first amorphous silicon layer, a second carbon layer, a second amorphous silicon layer, and a third carbon layer. In this preferred embodiment of the present invention, the first carbon layer and the second carbon layer can effectively buffer the stress and longitudinal expansion of the first amorphous silicon layer and the second amorphous silicon layer and enhance the interfacial contact, further effectively reducing electrode pulverization caused by volume expansion; together with the third carbon layer, it effectively protects each amorphous silicon layer, facilitates the coating of the silicon-carbon composite layer, and improves the wettability of the electrolyte, thereby further improving cycle stability and increasing energy density.
[0050] More preferably, the thickness of the first carbon layer and the second carbon layer are each independently 30-200 nm, and the thickness of the third carbon layer is 200-1000 nm, more preferably 210-1000 nm, and even more preferably 300-1000 nm. In a preferred embodiment of the present invention, the thickness of the third carbon layer is greater than or equal to the thickness of the first carbon layer and the second carbon layer, which is more conducive to forming a carbon coating structure with higher flexibility and buffering capacity on the outer layer of the electrode. This absorbs the volume expansion stress of amorphous silicon during charging and discharging, prevents cracking or pulverization and detachment of the active layer surface, and improves the wettability and interfacial stability of the electrolyte, ultimately further enhancing the cycle life and overall electrochemical performance.
[0051] In some preferred embodiments of the present invention, the thickness of the second carbon layer is less than the thickness of the third carbon layer, and the thickness of the second carbon layer is not greater than the thickness of the first carbon layer. This preferred approach facilitates the construction of a gradient carbon structure with a dense, conductive inner layer and a buffered outer layer in the deposition direction, thereby reducing stress concentration caused by volume expansion and further improving film adhesion and structural integrity.
[0052] Preferably, the thickness of the second carbon layer is 30-100 nm.
[0053] In some preferred embodiments of the present invention, the ratio of the thickness of the second carbon layer to the thickness of the third carbon layer is 1:(2-15), more preferably 1:(3-15). This preferred embodiment further enhances cycle life and overall electrochemical performance.
[0054] Preferably, the carbon layer material comprises at least one of amorphous carbon, hydrogenated amorphous carbon, and nitrogen-doped carbon, which is more conducive to forming a protective structural layer with both conductivity and chemical stability between the electrode layers, thereby further enhancing cycle life and overall electrochemical performance. Nitrogen-doped carbon refers to carbon material doped with nitrogen.
[0055] Preferably, the negative electrode material further includes a protective layer disposed between the copper-containing substrate and the carbon / amorphous silicon alternating layer, the protective layer comprising a titanium nitride layer. The titanium nitride layer, as a dense protective layer between the carbon / amorphous silicon alternating layer and the copper-containing substrate, can prevent corrosion caused by the reaction of copper in the copper-containing substrate with the electrolyte, and provides low contact resistance and high stability, further improving the battery's energy density and cycle stability.
[0056] Preferably, the thickness of the protective layer is 10-100 nm, specifically 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 95 nm or 100 nm, and any range between two point values.
[0057] In some preferred embodiments of the present invention, the protective layer further includes a titanium layer located on the side of the titanium nitride layer away from the copper-containing substrate. The preferred embodiment of a stacked protective layer including a titanium nitride layer and a titanium layer facilitates the formation of a gradient protective structure with both high adhesion and excellent barrier properties between the copper-containing substrate and the active layer. This effectively prevents copper migration and interfacial oxidation, improves film adhesion and chemical stability, and thus significantly enhances the cycle stability and conductivity reliability of the electrode material.
[0058] More preferably, the thickness ratio of the titanium layer to the titanium nitride layer is (0.1-0.7):1, specifically, it can be 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, or 0.7:1, or any range between two values. This preferred scheme is more conducive to achieving excellent barrier and protective performance while ensuring interfacial adhesion, thereby achieving a balanced optimization of bonding strength and chemical stability.
[0059] Preferably, the thickness of the titanium layer is 5-20 nm, specifically 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm, and any range between two point values.
[0060] Preferably, the thickness of the titanium nitride layer is 30-80 nm, specifically 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 79 nm or 80 nm, and any range between two point values.
[0061] In some preferred embodiments of the present invention, the copper-containing substrate includes copper foil.
[0062] In a second aspect, the present invention provides a method for preparing a negative electrode material, the method comprising: depositing a carbon / amorphous silicon alternating layer on the surface of a copper-containing substrate, and then forming a silicon-carbon composite layer on the surface of the carbon / amorphous silicon alternating layer; wherein, the process of depositing the carbon / amorphous silicon alternating layer comprises alternating deposition of carbon layers and amorphous silicon layers.
[0063] In some preferred embodiments of the present invention, the preparation method further includes: depositing a protective layer between a copper-containing substrate and a silicon-carbon composite layer.
[0064] More preferably, the process of depositing the protective layer includes: sequentially depositing a titanium nitride layer and a titanium layer.
[0065] In some preferred embodiments of the present invention, the protective layer is deposited using the PVD method.
[0066] In some preferred embodiments of the present invention, the alternating carbon / amorphous silicon layers are deposited using a PECVD process. More preferably, the PECVD process temperature is 200-500°C. The structure of the present invention can be achieved using a low-temperature PECVD process at 200-250°C. Furthermore, the gas introduced during the PECVD process can be determined based on the desired deposited film layer. For example, CH4 and H2 gases can be introduced during carbon layer deposition, and SiH4, H2, and Ar gases can be introduced during amorphous silicon layer deposition, as long as the target film layer is obtained.
[0067] In some preferred embodiments of the present invention, the silicon-carbon composite layer is formed by coating.
[0068] Thirdly, the present invention provides a lithium battery comprising a positive electrode material, a negative electrode material as described in the first aspect, a separator, and an electrolyte.
[0069] In some preferred embodiments of the present invention, the cathode material is a lithium manganese iron phosphate cathode material, which includes a lithium manganese iron phosphate matrix and a carbon coating layer covering the surface of the lithium manganese iron phosphate matrix; the chemical formula of the lithium manganese iron phosphate matrix is Li. a Fe x Mn y M j PO q Wherein, M includes at least one of Al, Mg, Cu, Co, Ni, Nb, V, Ti, and La; 0.8≤a≤1.2, 0.1≤x≤0.9, 0.1≤y≤0.9, 0≤j≤0.1, and 4≤q≤5; the mass of the carbon coating layer accounts for 0.5%-3% of the total mass of the lithium manganese iron phosphate cathode material.
[0070] This invention rationally controls the values of a, x, y, j, and q in the chemical formula of lithium manganese iron phosphate matrix, thereby effectively improving the electrochemical performance of lithium manganese iron phosphate cathode materials. Specifically, adjusting the value of a controls the number of lithium vacancies in the crystal lattice, thus affecting lithium-ion diffusion kinetics and structural stability. Adjusting the value of x controls the iron content, thus affecting the voltage plateau and electronic conductivity. Adjusting the value of y controls the manganese content, thus determining the high voltage plateau. Adjusting the value of j controls the dopant element content, optimizing the material structure through bulk doping or surface modification. Adjusting the value of q controls the phosphorus-oxygen ratio, maintaining the stability of the olivine structure and regulating the lattice energy. Preferably, the carbon coating layer accounts for 0.5% to 3% of the total mass of the lithium manganese iron phosphate cathode material, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, and any value between them. In this invention, the carbon content within the above range can balance the conductivity and specific surface area of the cathode material, thereby improving the electrochemical performance, compaction density, and interfacial stability of the cathode material.
[0071] In some preferred embodiments of the present invention, the electrolyte comprises an electrolyte, additives, and a solvent, wherein the electrolyte comprises lithium hexafluorophosphate. Lithium hexafluorophosphate exhibits excellent overall performance in conventional carbonate solvent systems. It has high solubility and ionic conductivity in commonly used organic carbonate solvents (such as EC, DMC, DEC, and EMC), and can form a stable interface film (SEI / CEI) with graphite anode and high-voltage cathode materials. These characteristics are crucial for ensuring the high-rate charge-discharge performance, long cycle life, and safety of the battery.
[0072] In this invention, the additives and solvents can be any corresponding types found in the prior art. For example, additives may include vinylene carbonate and tris(trimethylsilane) phosphate, etc. Solvents can be organic solvents and non-organic solvents. In some preferred embodiments of this invention, the organic solvent may include cyclic carbonates and / or chain carbonates. More preferably, the cyclic carbonates include at least one of ethylene carbonate, propylene carbonate, and butene carbonate. More preferably, the chain carbonates include at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate.
[0073] Fourthly, the present invention provides an electrical device comprising the lithium battery described in the third aspect.
[0074] The electrical devices include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems. To meet the high power and high energy density requirements of lithium manganese iron phosphate (LFP) batteries for these devices, battery packs or battery modules can be used. The electrical devices can also be mobile phones, tablets, laptops, etc.; these types of devices typically require a slim and lightweight design and can also use LFP batteries as their power source.
[0075] The embodiments of the present invention described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0076] Example 1
[0077] A negative electrode material, such as Figure 1 As shown, the structure includes a copper foil 1, a protective layer 2 deposited on the copper foil 1 using a PVD method, followed by the deposition of a carbon / amorphous silicon alternating layer 3 on the protective layer 2 using a PECVD low-temperature process at 230°C, and then a silicon-carbon composite layer 4 (with a silicon content of 10 wt%) coated on the carbon / amorphous silicon alternating layer 3. The protective layer 2 includes a titanium nitride layer with a thickness of 40 nm and a titanium layer with a thickness of 10 nm, which are sequentially disposed. The total thickness of the protective layer 2 is 50 nm, the thickness ratio of the titanium layer to the titanium nitride layer is 0.25:1, and the thickness of the silicon-carbon composite layer 4 is 10 µm. Along the direction away from the copper-containing substrate along the protective layer 2, the carbon / amorphous silicon alternating layer 3 sequentially includes a first carbon layer 31, a first amorphous silicon layer 32, a second carbon layer 33, a second amorphous silicon layer 34, and a third carbon layer 35. The thickness of the first carbon layer 31 and the second carbon layer 33 is 100 nm, the thickness of the third carbon layer 35 is 500 nm, the thickness of the first amorphous silicon layer 32 and the second amorphous silicon layer 34 is 2.5 µm, and the total thickness of the carbon / amorphous silicon alternating layer 3 is 5.7 µm.
[0078] The above-mentioned negative electrode material and positive electrode material (the positive electrode material is LiFe) are combined. 0.4 Mn 0.6 The components, including PO4 / C (C content of 1.5wt%), electrolyte (specifically lithium hexafluorophosphate LiPF6), and separator, are assembled into a lithium button battery.
[0079] Example 2
[0080] The same procedure was carried out as in Example 1, except that the thickness of the first carbon layer 31 in the carbon / amorphous silicon alternating layer 3 was 200 nm.
[0081] Example 3
[0082] The same procedure was performed as in Example 1, except that the thickness of the third carbon layer 35 was 1000 nm.
[0083] Example 4
[0084] The same procedure was performed as in Example 1, except that the thickness of the third carbon layer 35 was 200 nm.
[0085] Example 5
[0086] The process was carried out in accordance with Example 1, except that the carbon / amorphous silicon alternating layer 3 was composed of carbon layer A, amorphous silicon layer A and carbon layer B deposited sequentially. The thickness of carbon layer A was 200 nm, the thickness of amorphous silicon layer A was 5 µm and the thickness of carbon layer B was 500 nm.
[0087] Example 6
[0088] The same procedure was carried out with reference to Example 1, except that the thickness of the first amorphous silicon layer 32 was 2µm and the thickness of the second amorphous silicon layer 34 was 4µm.
[0089] Example 7
[0090] The procedure was carried out in accordance with Example 1, except that no titanium layer was formed in the protective layer 2.
[0091] Example 8
[0092] The same procedure was followed as in Example 1, except that the thickness of the silicon-carbon composite layer 4 was 6µm.
[0093] Comparative Example 1
[0094] The procedure was carried out in accordance with Example 1, except that no alternating carbon / amorphous silicon layer 3 was deposited.
[0095] Comparative Example 2
[0096] The process was carried out in accordance with Example 1, except that the carbon / amorphous silicon alternating layer 3 was replaced with a pure amorphous silicon layer, i.e., no carbon layer was provided, and the thickness of the pure amorphous silicon layer was the same as the total thickness of the amorphous silicon layer contained in the carbon / amorphous silicon alternating layer 3 in Example 1.
[0097] Comparative Example 3
[0098] The procedure was carried out in accordance with Example 1, except that no protective layer 2 was deposited.
[0099] Comparative Example 4
[0100] The same procedure was performed as in Comparative Example 1, except that the thickness of the silicon-carbon composite layer 4 was 40µm.
[0101] Test case
[0102] The batteries obtained in the above embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1.
[0103] The material cost is based on the cost of the materials used in Example 1 (normalized to 1.000), and the costs of other examples are expressed as relative values of this benchmark.
[0104] Cyclic life test method:
[0105] (1) Expected cycle life at 25℃: At 25℃, the first cycle is performed at 0.1C / 0.1C, followed by continuous charge-discharge cycles at 0.5C / 0.5C. After 50 cycles, the number of cycles corresponding to the capacity retention rate dropping to 80% is extrapolated based on the capacity decay slope. The expected cycle life at 25℃ is then calculated.
[0106] (2) Expected cycle life at 45℃: At 45℃, the first cycle is performed at 0.1C / 0.1C, followed by continuous charge-discharge cycles at 0.5C / 0.5C. After 50 cycles, the expected cycle life at 45℃ is calculated by extrapolating the capacity decay slope to the number of cycles corresponding to the capacity retention rate dropping to 80%.
[0107] The expansion rate was measured using in-situ thickness measurements.
[0108] (1) Apparatus: a spring-loaded button battery clamp (constant voltage), a dial gauge / inductive displacement meter (resolution ≤1 µm).
[0109] (2) Steps: An external micro displacement gauge is placed on the spring-loaded button cell clamp, and the spring force is set to approximately constant. Charge and discharge at the target rate at room temperature, continuously record the change in the total thickness of the casing, and calculate the expansion rate of the thickness change. The electrode contribution is estimated by pre-calibrating the empty shell / separator / casing thickness; or it can be directly used as the overall cell expansion index for engineering comparison. Specific capacity test method: Constant current-constant voltage charge and discharge test is performed at 25℃ with a fixed current of 0.5C, and the actual discharge capacity is divided by the mass of active material.
[0110] Table 1
[0111] Performance indicators Material costs Expected cycle life (cycles) at 25℃ (room temperature) Expected cycle life at 45℃ (times) Capacity (mAh / g) Expansion rate (thickness change) Example 1 1.000 1000 600 1800 15% Example 2 1.000 1030 600 1800 14.9% Example 3 1.001 1100 630 1800 14.5% Example 4 1.000 990 550 1800 16.2% Example 5 0.993 900 520 1800 17.5% Example 6 1.005 992 560 1820 16.6% Example 7 0.998 998 595 1800 15.1% Example 8 0.980 1000 600 1765 15% Comparative Example 1 0.520 500 200 350 29.3% Comparative Example 2 0.960 550 230 1720 27.3% Comparative Example 3 0.996 850 350 1800 15.6% Comparative Example 4 1.960 500 200 1400 30%
[0112] The results above show that, compared with the comparative example, the embodiment of the present invention can improve rate performance and cycle life, increase battery capacity, significantly reduce material costs compared with existing solutions using thicker silicon-carbon composite layers for anode materials, and improve battery stability and cycle stability.
[0113] Furthermore, as can be seen from Examples 1 and 2-8, the preferred scheme of the present invention is more conducive to improving rate performance and cycle life, increasing battery capacity, significantly reducing material costs, and enhancing cycle stability.
[0114] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The material includes a copper-containing substrate, on which a carbon / amorphous silicon alternating layer and a silicon-carbon composite layer are sequentially disposed. In the direction away from the copper-containing substrate, the carbon / amorphous silicon alternating layer sequentially comprises a first carbon layer, a first amorphous silicon layer, a second carbon layer, a second amorphous silicon layer, and a third carbon layer. The thickness of the second carbon layer is less than the thickness of the third carbon layer, and the thickness of the second carbon layer is less than the thickness of the first carbon layer. The thicknesses of the first and second carbon layers are each independently 30 nm-200 nm, the thickness of the third carbon layer is 200-1000 nm, and the thickness of a single amorphous silicon layer is 1-5 µm. The total thickness of the carbon / amorphous silicon alternating layer is 3-15 µm, the thickness of the silicon-carbon composite layer is 5-15 µm, and the silicon content in the silicon-carbon composite layer is 5-20 wt%.
2. The negative electrode sheet according to claim 1, characterized in that, The thickness of the second carbon layer is 30-100 nm.
3. The negative electrode sheet according to claim 1, characterized in that, The carbon layer material includes at least one of amorphous carbon, hydrogenated amorphous carbon, and nitrogen-doped carbon.
4. The negative electrode sheet according to claim 1, characterized in that, The negative electrode also includes a protective layer disposed between a copper substrate and an alternating carbon / amorphous silicon layer, the protective layer including a titanium nitride layer.
5. The negative electrode sheet according to claim 4, characterized in that, The thickness of the protective layer is 10-100 nm.
6. The negative electrode sheet according to claim 4, characterized in that, The protective layer also includes a titanium layer located on the side of the titanium nitride layer away from the copper-containing substrate.
7. The negative electrode sheet according to claim 6, characterized in that, The thickness ratio of the titanium layer to the titanium nitride layer is (0.1-0.7):
1.
8. The negative electrode sheet according to claim 6, characterized in that, The thickness of the titanium layer is 5-20 nm, and the thickness of the titanium nitride layer is 30-80 nm.
9. The negative electrode sheet according to claim 1, characterized in that, Copper-containing substrates include copper foil.
10. A method for preparing a negative electrode sheet, characterized in that, It is used to prepare a negative electrode sheet as described in any one of claims 1-9. The preparation method includes: depositing a carbon / amorphous silicon alternating layer on the surface of a copper-containing substrate, and then forming a silicon-carbon composite layer on the surface of the carbon / amorphous silicon alternating layer; wherein, the process of depositing the carbon / amorphous silicon alternating layer includes alternating deposition of carbon layers and amorphous silicon layers.
11. The method for preparing the negative electrode sheet according to claim 10, characterized in that, The preparation method also includes at least one of the following processes: Process 1, the preparation method also includes: depositing a protective layer between the copper-containing substrate and the silicon-carbon composite layer, the process of depositing the protective layer includes: depositing a titanium nitride layer or sequentially depositing a titanium nitride layer and a titanium layer; Process 2: Deposition of alternating carbon / amorphous silicon layers is performed using PECVD technology at a temperature of 200-500℃. Process 3: The silicon-carbon composite layer is formed by coating.
12. A lithium battery, characterized in that, It includes a positive electrode material, a negative electrode sheet as described in any one of claims 1-9, a separator, and an electrolyte.
13. The lithium battery according to claim 12, characterized in that, The cathode material is lithium manganese iron phosphate cathode material, which includes a lithium manganese iron phosphate matrix and a carbon coating layer covering the surface of the lithium manganese iron phosphate matrix; the chemical formula of the lithium manganese iron phosphate matrix is Li. a Fe x Mn y M j PO q Wherein, M includes at least one of Al, Mg, Cu, Co, Ni, Nb, V, Ti, and La; 0.8≤a≤1.2, 0.1≤x≤0.9, 0.1≤y≤0.9, 0≤j≤0.1, and 4≤q≤5; the mass of the carbon coating layer accounts for 0.5%-3% of the total mass of the lithium manganese iron phosphate cathode material.
14. The lithium battery according to claim 12, characterized in that, The electrolyte contains an electrolyte, additives, and a solvent; the electrolyte includes lithium hexafluorophosphate.
15. An electrical appliance, characterized in that, It includes the lithium battery as described in any one of claims 12-14.
Citation Information
Patent Citations
Method for preparing carbon-silicon negative electrode material through heat treatment process
CN108807840A
Diffusion barrier films enabling the stability of lithium
CN112292775A
Integrated negative electrode material composed of 3D current collector, carbon layer and silicon layer
CN115394956A